Virology and cancer biology: the retroviruses and the discovery of oncogenes - Enquist, Lynn W. (Henry Stewart Talks, 2020)
Virology and cancer biology, Modest subset of all viruses associated with cancer, Viruses as initiators of oncogenesis by replication modes, Cancer formation as a byproduct of virus life cycle, Retroviruses and oncogenes, Hepatitis viruses